Historical Foundations and Theological Principles of Jabariyah and Qadariyah Doctrines - W, Walib; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines the historical background and main ideas of two major schools in classical Islamic theology, Jabariyah and Qadariyah. These theological movements emerged as responses to the fundamental question concerning the relationship between human free will and the absolute power of Allah SWT. The Jabariyah school asserts that all human actions are predetermined by divine decree (qadha and qadar), leaving no room for free will. In contrast, the Qadariyah school maintains that human beings possess freedom of choice and moral responsibility for their actions. This study employs a qualitative descriptive method with a library research approach to explore the theological foundations, historical contexts, and points of convergence and divergence between the two schools. The findings reveal that the debate between Jabariyah and Qadariyah was not merely theological but also carried political and philosophical dimensions, exerting a significant influence on the subsequent development of Islamic theology.